2014
DOI: 10.1002/art.38237
|View full text |Cite
|
Sign up to set email alerts
|

A Single Functional Group Substitution in C5a Breaks B Cell and T Cell Tolerance and Protects Against Experimental Arthritis

Abstract: Objective Deficiency in complement factor 5 (C5) protects against arthritis development. However, there is currently no approach translating these findings successfully into arthritis therapy, as by targeting the key component, C5a. Methods We generated an anti-C5a vaccine by incorporating the unnatural amino acid p-nitrophenylalanine (4NPA) at selected sites into murine C5a. C5a-4NPA variants were screened for their immunogenicity on different arthritis susceptiple MHCII backgrounds. A vaccine candidate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…It is also noteworthy that while Arg 37 display the highest fluctuation in h C5a, the Tyr 36 display the highest fluctuation in m C5a. Interestingly, mutation of Tyr 36 in m C5a (Figure 2(c)) to NPA (p-nitrophenyl alanine) has recently been shown to produce an anti-m C5a vaccine (Kessel et al, 2014), effective against the collagen-induced arthritis (Kessel et al, 2014). Similarly, previous mutational studies have also identified Arg 37 as a potential pharmacophore that affect the potency of h C5a toward C5aR (Kola, Baensch, Bautsch, Klos, & Kohl, 1999;Toth et al, 1994).…”
Section: Identifying the Allosteric Switch Region On H C5amentioning
confidence: 93%
“…It is also noteworthy that while Arg 37 display the highest fluctuation in h C5a, the Tyr 36 display the highest fluctuation in m C5a. Interestingly, mutation of Tyr 36 in m C5a (Figure 2(c)) to NPA (p-nitrophenyl alanine) has recently been shown to produce an anti-m C5a vaccine (Kessel et al, 2014), effective against the collagen-induced arthritis (Kessel et al, 2014). Similarly, previous mutational studies have also identified Arg 37 as a potential pharmacophore that affect the potency of h C5a toward C5aR (Kola, Baensch, Bautsch, Klos, & Kohl, 1999;Toth et al, 1994).…”
Section: Identifying the Allosteric Switch Region On H C5amentioning
confidence: 93%
“…The vaccine itself lead to a loss of B and T-cell tolerance to C5a in mice whose cells expressed the particular receptor “class II MHC H-2(q).” Both the indigenous C5a and modified C5a induced antibodies capable of effectively neutralizing C5a. The high titers of IgG prevented disease development, but did not reverse the course of ongoing disease [75]. …”
Section: Therapeutic Use Of C5amentioning
confidence: 99%
“…15 In addition, pNO 2 Phe-containing self-antigens induced a protective cross-reactive immune response without the need for strong adjuvants and resulted in high titers for at least 4 months in mice. 16 Thus, we decided to assess whether endogenous protein variants containing pNO 2 Phe are able to trigger a humoral immune response in vitro.…”
Section: Introductionmentioning
confidence: 99%